Provoking progress: a new chapter - Vivian Siegel (The Company of Biologists, 2013)
Summary Journals do more than publish collections of research articles and reviews; they also create community, influence standards for community behavior and 'provoke progress' in a particular field. In this Editorial, founding Editor-in-Chief Vivian Siegel compares launching a journal to raising a child, and reflects on the choices and successes of her tenure at DMM as she passes the leadership of the journal to new editors.